Predicting band offset of lattice matched ZnO and BeCdO heterojunction from first principles. Issue 6 (3rd June 2019) - Liu, Xiaojie; Chen, Junli; Yin, Hang; Bai, Lina; Yao, Chengbao; Li, Hua; Yin, Haitao; Wang, Yin
ABSTRACT: Using first-principles approach, we calculated the band gaps of wurtzite Be 1 − x Cd x O ternary alloy and the band offset of the lattice matched ZnO / Be 0.44 Cd 0.56 O [ 1 1 2 ¯ 0 ] heterojunction, where the modified Becke–Johnson semi-local exchange was used to determine the band gap and the coherent potential approximation was applied to deal with doping effect in disordered alloys. The ZnO / Be 0.44 Cd 0.56 O heterojunction was determined to have a type II band alignment, with valence and conduction band offset being 0.28 and 0.50 eV, respectively. The calculation approach and procedure demonstrated here can be used to predict the band offset of more lattice matched semiconductor heterojunctions. GRAPHICAL ABSTRACT: IMPACT STATEMENT: The band offsets of lattice matched ZnO / Be 0.44 Cd 0.56 O heterojunction were predicted from first principles, where band gaps of semiconductors and configuration average of disorders were both accurately and efficiently calculated.